Stigma and self-perceived burden in postoperative liver cancer patients: the mediating role of financial toxicity - Zhang, Yue; Cao, Yiqin; Wang, Yanyan; Wang, Di; Ye, Hongfang; Nie, Chunlei (Frontiers in Psychiatry, 2025)
PurposeTo investigate the mediating effect of financial toxicity on stigma and self-perceived burden in patients with liver cancer after surgery.MethodsUsing a convenience sampling method, 236 postoperative liver cancer patients treated at a tertiary hospital in Nanjing from April 2024 to July 2024 were selected for the study. Questionnaires were administered, including a general information survey, the Social Impact Scale (SIS), the Self-Perceived Burden Scale for Cancer Patients (SPBS-CP), and the Comprehensive Score for Financial Toxicity-Functional Assessment of Chronic Illness Therapy Version 2 (COST-FACIT-V2). Data were analyzed using SPSS 22.0 for descriptive statistics, correlation analysis, and regression analysis. MPlus 8.3 was employed to examine the mediating effect of financial toxicity between stigma and self-perceived burden, and the Bootstrap method was used to test the significance of the mediation effect.ResultsThe self-perceived burden score, stigma score, and financial toxicity score were (31.72 ± 7.52), (58.92 ± 8.69), and (18.62 ± 6.80), respectively. The financial toxicity and self-perceived burden were negatively correlated (r=−0.270,P=0.001). There was a positive correlation between stigma and self-perceived burden (r=0.586,P=0.000). Financial toxicity partially mediated the relationship between stigma and self-perceived burden, accounting for 4.84% of the total effect.ConclusionStigma can influence the self-perceived burden of liver cancer patients through financial toxicity. Clinical nurses should prioritize alleviating patients’ stigma while also paying close attention to their financial toxicity status, providing feasible assistance in a timely manner to reduce their self-perceived burden.